Low-energy 6D, N=(1,1) SYM effective action beyond the leading approximation - I.L. Buchbinder; E.A. Ivanov; B.S. Merzlikin (Nuclear Physics B, 2020)
For 6D, N=(1,1) SYM theory formulated in N=(1,0) harmonic superspace as a theory of interacting gauge multiplet and hypermultiplet we construct the N=(1,1) supersymmetric Heisenberg-Euler-type superfield effective action. The effective action is computed for the slowly varying on-shell background fields and involves, in the bosonic sector, all powers of a constant abelian strength.